Synthetic Protocols towards Selenacalix[3]triazines - Thomas, Joice; Van Rossom, Wim; Van Hecke, Kristof; Van Meervelt, Luc; Smet, Mario; Maes, Wouter (Synthesis, 2013)
Selenium-bridged heteracalixarenes were synthesized by convenient one-pot SNAr reactions starting from variously 2-substituted 4,6-dichloro-1,3,5-triazine building blocks. Reactions of these precursors with sodium hydroselenide afforded the selenacalix[3]triazines as the only macrocyclic products. Yields of the cyclotrimers were significantly increased by optimization of the macrocyclization conditions, the optimum parameters being dependent on the triazine functionalization pattern. X-ray diffraction studies allowed unambiguous identification of the structures and comparison with the solid-state features of analogous heteracalixarenes.
Keywords: (hetera)calixarenes; macrocycles; selenium; 1,3,5-triazines; substituent effects